PENGARUH KEADILAN PROSES SELEKSI DAN PENYEBARAN INFORMASI TERKAIT SELEKSI TERHADAP DAYA TARIK ORGANISASI - Yudiari, Winda; Rahyuda, Agoes Ganesha (E-Jurnal Manajemen, 2015)
An organization's reputation can be seen from how attractive the organization in attracting potential candidates, who want to work in the organization. Therefore, the organization attractiveness from the employee perspective should be noticed. But until now, there was few studies that explore the role of the selection system in enhancing the organization's attractiveness. This study aims to understand the influence of selection fairness perception and information sharing fairness perspection of organization attractiveness.In this study, the selected content is a public organization in the Negara Distric, that is the village office. The amount of sample used in this study is 32 people. Data was collected by questionnaire, and the data were analyzed using multiple linear regression analysis technique. The results showed that the selection fairness perception and information sharing fairness percpetion related to the selection affects the organization attractivenss. In addition, it is known that the information sharing fairness perception have bigger influence rather than selection fairness perception of organization attractiveness.
Keywords: selection fairness perceptions, information sharing fairness perceptions, organizational attractiveness